The effects of work:rest duration on physiological and perceptual responses during intermittent exercise and performance - Price, M.; Moss, P. (Journal of Sports Sciences, 2007)
In this study, we examined the effects of different work:rest durations during 20 min intermittent treadmill running and subsequent performance. Nine males (mean age 25.8 years, s = 6.8; body mass 73.9 kg, s = 8.8; stature 1.75 m, s = 0.05; O2max 55.5 ml/kg·min, s = 5.8) undertook repeated sprints at 120 % of the speed at which O2max was attained interspersed with passive recovery. The work:rest ratio was constant (1:1.5) with trials involving either short (6:9 s) or long (24:36 s) work:rest exercise protocols (total exercise time 8 min). Each trial was followed by a performance run to volitional exhaustion at the same running speed. Testing order was randomized and counterbalanced. Heart rate, oxygen consumption, respiratory exchange ratio, and blood glucose were similar between trials (P > 0.05). Blood lactate concentration was greater during the long than the short exercise protocol (P < 0.05), whereas blood pH was lower during the long than the short exercise protocol (7.28, s = 0.11 and 7.30, s = 0.03 at 20 min, respectively; P < 0.05). Perceptions of effort were greater throughout exercise for the long than the short exercise protocol (16.6, s = 1.4 and 15.1, s = 1.6 at 20 min, respectively; P < 0.05) and correlated with blood lactate (r = 0.43) and bicarbonate concentrations (r = -0.59; P < 0.05). Although blood lactate concentration at 20 min was related to performance time (r = -0.56; P < 0.05), no differences were observed between trials for time to exhaustion (short exercise protocol: 95.8 s, s = 30.0; long exercise protocol: 92.0 s, s = 37.1) or physiological responses at exhaustion (P > 0.05). Our results demonstrate that 20 min of intermittent exercise involving a long work:rest duration elicits greater metabolic and perceptual strain than intermittent exercise undertaken with a short work:rest duration but does not affect subsequent run time to exhaustion.